LEGACY IN DIFFERENT RELIGION AND THE IMPLEMENTATION OF WAJIBAH HERITAGE AGAINST NON MOSLEM HEIR IN INDONESIAN - I Nyoman Sujana (NOTARIIL Jurnal Kenotariatan, 2020)
This study examines more deeply about the judge's consideration in establishing a Muslim as an heir of the assets of a non-Muslim heir in Indonesia, and why wajibah must be chosen as a solution in providing inheritance to non-Muslim heirs in Indonesia. This research is a normative legal research by using statute approach conceptual approach and case approach. The result showed that firstly the judges' considerations that deviate from the Word of the Prophet (peace be upon him): "It is not right for a Muslim to inherit unbelievers, nor do infidels inherit Muslims" is based on the values of justice and legal certainty regarding the rights of heirs to the inheritance arising from the relationship of the heirs arising from the relationship kinship that is so close and peaceful despite different beliefs/different religions, the ability of Muslim heirs to receive inheritance from non-Muslim heirs will bring more kemashalatan (goodness) for Islam. By leaving the inheritance of non-Muslim heirs to Muslim heirs, it will safeguard these assets to bring good deeds in accordance with the teachings in Islam. Secondly, mandatory wills are chosen as a way out in giving inheritance to non-Muslim heirs, because the heir does not leave a will or grant during his lifetime to non-Muslim heirs, so that for the sake of fairness, usefulness and legal certainty, the judge with his authority has the authority to determine compulsory testaments to non-Muslim heirs. Because the kinship system in Islamic law is more important when compared to religious differences as a barrier to inheritance.